ANALISIS PERBEDAAN FAKTOR RISIKO KEJADIAN DEMAM BERDARAH DENGUE ANTARA DAERAH ENDEMIS DAN DAERAH SPORADIS - Laily Khairiyati; Rudi Fakhriadi (Lambung Mangkurat, 2019)
Dengue Hemorrhagic Fever (DHF) is one of several infectious diseases which is a health problem in the world, especially developing countries. The purpose of this study was to determine the differences in larvae and behavior index of eradication of mosquito nests (PSN) in endemic areas and sporadic areas of Dengue Hemorrhagic Fever in Banjarbaru City. The research design used was a cross-sectional study using a simple random sampling technique with a sample of 100 respondents. Research instruments using a questionnaire. Observation sheet. The results of the analysis showed that there was no relationship between knowledge of mosquito nest eradication and the incidence of dengue in individuals or families in endemic areas (p-value = 0.088) and sporadic areas (p-value = 1.000). There is no relationship between the attitude of eradicating mosquito nests and the incidence of DHF in endemic area individuals/families (p-value = 0.271). There is no relationship between mosquito nest eradication and the incidence of dengue in individuals/families in endemic areas (p-value = 0.710) and (p-value = 0.230) in sporadic areas. Thus It can be concluded that the knowledge, attitudes, and actions of a good person will prevent the occurrence of DHF in individuals/families.